Growth retardants in dry bean plants: impacts on the architecture, photoassimilate partition, and their consequences on the yield - Carvalho, Márcia Eugênia Amaral de; Castro, Paulo Roberto de Camargo; Dias, Kaio Manoel de Freitas; Ferraz Júnior, Marcos Vinícius de Castro (Agrarian, 2013)
The objective of this study was to evaluate the effects of three growth retardants on the development and yield of dry bean plants. The treatments were control (water), maleic hydrazide (0.09 g a.i. L-1), ethyl-trinexapac (0.5 g a.i. L-1) and propiconazole (0.125 g a.i. L-1). Maleic hydrazide decreased the plant growth rate, resulting in the height reduction (46%). It also inhibited the twining shoot development, thus controlling the vigor excess of this genotype which has indeterminate growth. On the other hand, plants which were treated with ethyl-trinexapac and propiconazole showed the higher heights (from 25 to 52%, respectively), indicating that both compounds provide the plant growth. These compounds also increased the number of pods (48 to 52%) and grains (47 to 102%), when compared to the control. However, ethyl-trinexapac and maleic hydrazide decreased 50-grain dry mass (41 to 52%), indicating changes in the photoassimilate partition among plant structures. This change was evidenced by the correlation coefficient of the biomass allocated between the shoots and grains, which was inversely proportional (r=-60.57) and highly significant (p=0.0002). It is concluded that maleic hydrazide is an efficient growth inhibitor of dry bean plants. Propiconazole and ethyl-trinexapac provide the plant growth, and also improve the main yield components. However, ethyl-trinexapac and maleic hydrazide decrease grain biomass.